Exploration of effective professional development characteristics from the perspective of integrated teaching project's coordinator, facilitator, and participants - Kurutaş, Büşra Sümeyye. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
It is quite important for policy makers and practitioners to invest in the most efficient learning environment for teachers to reinforce their learning and ultimately student achievement. Even though scholars are aware of Professional Development’s (PD) importance, review studies showed that effects of PDs are far from what is expected. Therefore, this phenomenological study aimed to discover effective PD characteristics by collecting data from each person with different roles involved in a PD. In this way, it was expected to discover remaining unknown aspects of maintaining effective PDs. Under the scope of this study, interviews were conducted with one PD coordinator, one facilitator, and five participants. Results supported each element of the effective PD consensus view. However, it was also discovered that even though some PD characteristics such as inclusion of assessment process, iterative and sustainable process, using instructional modellings, considering cognitive load, and PD venue were discussed in the literature, they were still overlooked. Additionally, new insights to the literature such as scope of the PD and learning how to learn were proposed and implications for future studies are offered.|Keywords : Professional Development, Online Professional Development, Teacher Learning, Teacher Change, Professional Development Effects on Classroom.
Keywords: Teachers -- Training of.